Architects in the General Government: Activities, Reckoning, Memory - Małgorzata Popiołek-Roßkamp (Zeitschrift für Ostmitteleuropa-Forschung, 2021)
The paper analyses architects as a professional group in General Government (GG) during the Second World War. It showcases some of their design work, projects, employment, education, and other aspects of everyday life in an occupied country. The focus is on architects working in three cities: the former Polish capital of Warsaw, the GG's new capital city of Cracow, and Zakopane, localized in the Tatra Mountains, which was intended to become a modern resort and sport center. The paper also mentions cases from Zamość and Radom. Most of the projects were realized by Polish architects employed by the German authorities. In Zakopane, Polish architects had a stronger position and more freedom in their work than in the other cities of GG. The article investigates the relationships between architecture and politics as well as the ideological impact of the architects' work. Using unpublished archival sources, it evaluates the post-war requitals of the German architect Hubert Groß and a Polish colleague Stefan Żychoń. Neither of the two had to face a court after the war due to his activity as an architect during the occupation. Groß was accused of having been a member in different Nazi organizations, and Stefan Żychoń was suspended from the Association of Polish Architects for one year. For political reasons, both German and Polish architects seldom included war-related activities in their official curricula after 1945. In Poland they remain a taboo until today.
Keywords: 710; architecture; city planning; architects; memory; General Governement; Poland; Germany